The Impact of Prostate Cancer and Hormonal Therapy on Bone - Andriole, Gerald L (MedReviews, LLC, 2009)
Large-scale studies agree that the observed decline in prostate cancer mortality that began in the early 1990s, shortly after prostate-specific antigen testing was introduced in the United States, is most likely explained by more widespread treatment of prostate cancer, including hormonal therapy. Practitioners should be aware of the risk of the development of osteoporosis and of skeletal side effects related to hormonal therapy to optimize the care of men with prostate cancer.